Analysis of the Development of the Transport System of Saint Petersburg - A. Yu. Smirnov (Мир новой экономики, 2021)
St. Petersburg is the fourth most populous city in Europe (after Moscow, Greater London and Greater Paris). Hundreds of thousands of people move daily within the urban agglomeration. Under these conditions, the effective functioning of the urban economy is impossible without a modern transport system capable of providing a solution to current and future problems of the urban economy. The work aims to analyse the effectiveness of the development of the transport system of St. Petersburg. Therefore, it is necessary to examine the main provisions of the most critical regulatory legal acts regulating the city's transport system's development, identify their advantages and disadvantages, and determine how effectively the activities outlined in them are being implemented in dynamics. The author's analysis of the two editions of the St. Petersburg transport system development program (the original edition of 2014 and the current edition of 2020) revealed negative trends, consisting of the deviation of the program indicators' actual value their planned values. Based on the results of the study, the author draws the following conclusions: when implementing the program for the development of the transport system of St. Petersburg, general principles of strategic management are not used, particularly, the effectiveness of program measures is not analysed, the reasons and factors that led to the deviation of planned indicators from the actual ones are not extended for a new period without any assessment of the results achieved; indicators of the transport system development program are constantly being adjusted downward; There is no unified management system for the development of transport infrastructure in the city, the program activities themselves are distributed among separate committees of the city administration, which harms the results of socio-economic development of the transport complex.